Artificial intelligence: Current and future impact on general practice. Issue 12 (December 2021) - Majekodunmi, Adedeji
We live in an age where a vast amount of information is being generated daily and this, combined with advances in computational power, provides fertile ground for numerous applications of artificial intelligence (AI). In medicine, we continue to see ground-breaking applications of AI, for example, in the detection of abnormalities on X-rays, skin lesion diagnostics, retinal image diagnostics and symptom triage. These applications have raised questions about the safety, ethics and limitations of AI in clinical diagnosis and patient care. There is no doubt that AI has much to offer clinicians in primary and secondary care. This article explores current and future applications of AI in primary care.